SIAPKAH INDONESIA MENGHADAPI MEA? - Christianus Yudi Prasetyo (EKONOMI & SOSIAL, 2017)
Countries that are members of the Association of South East Asian Nations (ASEAN) are facing an era where ASEAN turn into market and single production base, a highly competitive regional economic, equitable economic development, and a region fully integrated into global economy. That era is known as the ASEAN Economic Community (AEC), which take effect on January 2016. This literature survey was conducted to determine the position of Indonesia compared to other ASEAN countries based on existing statistical data so as to determine the readiness of Indonesia to face the AEC. Comparison is made on 6 ASEAN countries with the highest economic growth, namely: Singapore, Malaysia, Indonesia, Thailand, Philippines, and Brunei. It is important to know because many people are still not aware this intense competition in the era of AEC. Based on World Economic Forum, Indonesia is in 4th position after Singapore, Malaysia and Thailand in terms of competitiveness.